2021
DOI: 10.1093/europace/euab070
|View full text |Cite
|
Sign up to set email alerts
|

Increased beat-to-beat variability of cerebral microcirculatory perfusion during atrial fibrillation: a near-infrared spectroscopy study

Abstract: Aims Atrial fibrillation (AFib) is associated with cognitive decline/dementia, independently from clinical strokes or transient ischaemic attacks (TIA). Recent in silico data suggested that AFib may induce transient critical haemodynamic events in the cerebral microcirculation. The aim of this study is to use non-invasive spatially resolved cerebral near-infrared spectroscopy (SRS-NIRS) to investigate in vivo beat-to-beat microcirculatory perfusion during AFib and after sinus rhythm (SR) rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 17 publications
3
38
0
Order By: Relevance
“…A computational model of cerebral circulation during AF also demonstrated that the irregularity in cardiac cycles led to transient episodes of hypoperfusion and hypertension in the deep cerebral circle [ 5 , 6 ]. This finding was recently confirmed in vivo by spatially resolved cerebral near-infrared spectroscopy (SRS-NIRS): interestingly, restoration of sinus rhythm by cardioversion related to a reduction in the abnormal cerebral hemodynamic events and normalization of brain tissue perfusion [ 26 ]. In this respect, the Acute Cognitive Changes During Atrial Fibrillation Episodes (AFCOG) study will evaluate the acute effect of an AF episode on cognitive function (NCT04033510) in patients managed by rhythm control strategy [ 27 ].…”
Section: Discussionmentioning
confidence: 87%
“…A computational model of cerebral circulation during AF also demonstrated that the irregularity in cardiac cycles led to transient episodes of hypoperfusion and hypertension in the deep cerebral circle [ 5 , 6 ]. This finding was recently confirmed in vivo by spatially resolved cerebral near-infrared spectroscopy (SRS-NIRS): interestingly, restoration of sinus rhythm by cardioversion related to a reduction in the abnormal cerebral hemodynamic events and normalization of brain tissue perfusion [ 26 ]. In this respect, the Acute Cognitive Changes During Atrial Fibrillation Episodes (AFCOG) study will evaluate the acute effect of an AF episode on cognitive function (NCT04033510) in patients managed by rhythm control strategy [ 27 ].…”
Section: Discussionmentioning
confidence: 87%
“…-Extreme hemodynamic events: AF-related beat-to-beat variability, assessed by spatially resolved near-infrared spectroscopy, alters cerebral microvascular perfusion by inducing transient and repetitive hypoperfusions or hypertensive events in the deep cerebral circle. Interestingly, while these events disappear after sinus rhythm restoration by electrical cardioversion, the same does not occur in a comparable subgroup of AFL patients, supporting the hypothesis that a more regular ventricular response results less impacting on the deep cerebral circle ( 8 ).…”
mentioning
confidence: 71%
“…The latter hypothesis was also recently validated in vivo using spatially resolved cerebral near infrared spectroscopy (SRS-NIRS). Elective electrical cardioversion restoration sinus rhythm in persistent AF patients, significantly reduced beat-to-beat hypoperfusion and hypertensive events in the cerebral microcirculation, assessed by inter-beat differences of tissue hemoglobin index, an indirect index of tissue perfusion [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a causal relationship between AF (cause) and dementia (effect) has also been claimed [ 7 ]. In addition to the potential contribution of AF-related clinical cerebrovascular accidents (CVAs), there are several additional mechanistic hypotheses sustaining a causal association, which holds true also in the absence of CVAs: hemodynamic mechanisms (e.g., reduced mean cerebral blood flow, beat-to-beat alterations resulting in distal hypoperfusion and/or hypertensive events), subclinical microembolic cerebral infarctions, subclinical cerebral microbleeds (favored by oral anticoagulation treatment), and impaired cerebrovascular reactivity [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%